Kebijakan Penegakan Hukum Terhadap Kepemilikan Senjata Api Ilegal - Sandera, Denny; Pasalbessy, John Dirk; Salmon, Hendrik (PATTIMURA Legal Journal, 2022)
Introduction: Distribution and use of a firearms illegally in Maluku during social conflict in the last few years is often cause many problems. Because after the conflict, a fight between village often use a firearm. Since the conflict in 1999, the use of firearms both organic and local homemade, widely circulated in the community. Purposes of the Research: Examine the legislation approach on law enforcement againts illegal possesion of firearms in the Maluku Regional Police juridiction and the constraints that faced. Methods of the Research: This research is juridical normative, using various primary and secondary legal materials. Data analysis is descriptive qualitative. Results Originality of the Research: Lew enforcement againts firearms possesion and abuse crime done by oleh Maluku Regional Police in the form of preemptive, preventive and repressive acts. In the law enforcement, Maluku Regional Police not always done enforcement, but also applying discression by freeing from legal sanction for the owner of the firearms that willing voluntarily to gave the firearms that they have. The constraints faced in the law enforcement was internal (lack of personnel, equipment and facilities, lack of officers knowledge supervision) and external (regulation are no longer appropriate, wide area, weak coordination and society cooperation).